Efektivitas Penggunaan Media Belajar BigBook dalam Meningkatkan Kemampuan Membaca Peserta Didik Kelas 1 Sekolah Dasar Negeri 5 Jenggala - Lara Denisa; Heri Hadi Saputra, Muhammad Syazali, Lara Denisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of using Big Book learning media in improving the reading ability of grade I students at SD Negeri 5 Jenggala. The background of this study is based on the fact that the reading ability of early grade students is still relatively low. This requires a more innovative learning approach, one of which is through the use of visual media such as Big Book, which can attract attention and increase student involvement during the learning process. This study used a quantitative approach with an experimental design of One Group Pretest-Posttest Design. The sample in this study were all first grade students totaling 18 people. Data collection techniques were carried out through observation and giving initial tests (pretest) and final tests (posttest). The results showed an increase in the average score from the pretest result of 31.67 to 50.56 in the posttest. Data analysis was conducted using the paired sample t-test hypothesis test which showed a significance value of 0.000 (p < 0.05). This result shows that there is a significant difference between the pretest and posttest results after the application of Big Book media. Thus, it can be concluded that the use of Big Book learning media is effective in improving the reading ability of grade I students at SD Negeri 5 Jenggala. This finding is expected to be an input for early grade teachers in choosing the right learning media to improve students' literacy skills from an early age.